Zelluläre Pathophysiologie der pulmonalen Hypertonie - Kuebler, W. M. (Z Herz Thorax Gefasschir, 2014)
Pulmonary hypertension comprises a group of diseases with heterogeneous etiology characterized by an increase of hydrostatic pressure in the pulmonary vascular bed. While secondary pulmonary hypertension predominantly results from acute or chronic left ventricular failure, characteristic gene defects or predisposing risk factors lead to various forms of primary pulmonary hypertension. Despite its diverse pathogenesis, pulmonary hypertension exhibits a uniform cellular pathophysiology in the pulmonary microcirculation.    The dysfunction of lung vascular endothelial cells, which are the front line in response to hemodynamic changes in the pulmonary circulation, is the pathophysiological driving force of pulmonary hypertension. Endothelial dysfunction is characterized by a reduced production of vasodilative, anti-proliferative mediators and an increased release of vasoconstrictive, proliferative factors. This apparent imbalance not only enhances pulmonary vasoconstriction, but supports pathologic remodeling processes in the vascular intima and media. In addition, the pulmonary endothelium recruits platelets and leukocytes, thus, contributing to further release of vasoconstrictive and proliferative mediators and characteristic thrombus formation. These endothelium-derived pathomechanisms amplify each other, further enhance pulmonary vascular resistance, and finally result in fixation of the hypertensive state.    Hence, pulmonary hypertension not only describes an alteration of lung hemodynamics, but comprises a complex set of pathophysiological events in both lung parenchymal cells and circulating blood cells. For development of new therapeutical strategies, the multifactorial character of the disease should be considered.